Лідер філософсько-педагогічної науки – академік Іван Зязюн - Васянович, Григорій; Нагірняк, Михайло (НТУ "ХПІ", 2018)
У статті аналізується творча діяльність академіка Івана Зязюна в руслі філософсько-педагогічної проблематики. Увага зосереджується на дослідженні таких провідних ідей вченого: феномен людини і її діяльність; взаємозв'язок культури і освіти; морально-естетична парадигма діяльності вчителя; філософія педагогічної майстерності; процеси технологізації освіти; майбутнє професійної педагогіки. Автором доведено, що всі ці питання науковець вивчав на засадах філософсько-педагогічної антропології, екзистенціалізму, герменевтики і феноменології і був справжнім лідером у їх розробці і впровадженні у навчально-виховний процес системи освіти України. Формування духовно-моральних цінностей особистості учителя вченим пов'язується із його реальною свободою, можливостями самореалізації. Отже, всупереч зовнішнім обставинам людина має виявити свій власний проект.

The article analyzes academician Ivan Zyazun’s creative activity in the context of philosophical and pedagogical issues. Attention is focused on the study of such leading scholar’s ideas as the phenomenon of a person and his activities; the interconnection of culture and education; the moral and aesthetic paradigm of the teacher’s activity; the philosophy of pedagogical skill; the processes of technologization of education; the future of Professional pedagogy. All these questions are proved to be studied by a scientist on the principles of the philosophical and pedagogical anthropology, the existentialism, the hermeneutics and phenomenology and he was a real leader in their development and introduction into the educational process of the Ukrainian educational system. The scientist connects the formation of the spiritual and moral values of the teacher’s personality to his real freedom and the possibilities of his self-realization. Therefore, contrary to external circumstances, a person must identify his own project.
Leader of philosophical and pedagogical science – academician Ivan Zyazyun
Keywords: феномен людини; педагогічна майстерність; технологізація освіти; педагогіка майбутнього; pedagogical science; human phenomenon; pedagogical skill; technology education; pedagogy of the future